Urethane-based hot melt adhesive
Patent Information
- Application Number
- JP2020215003
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-27
- Filing Date
- 2020-12-24
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2040-12-24
Smart Images

Figure 0007651299000001 
Figure 0007651299000002 
Figure 0007651299000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a urethane-based hot melt adhesive. [Background technology]
[0002] In the past, various urethane-based hot melt adhesives have been proposed that contain a polymer having two functional groups capable of reacting with an isocyanate group, a polymer having three or more functional groups capable of reacting with an isocyanate group, a compound having a plurality of isocyanate groups, and a catalyst (see, for example, JP 2013-529238 A). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Special Publication No. 2013-529238 Summary of the Invention [Problem to be solved by the invention]
[0004] However, it has become clear that the above-mentioned urethane-based hot melt adhesives do not have sufficient resistance to moist heat, and do not exhibit sufficient adhesive properties in high temperature and high humidity environments.
[0005] Therefore, an object of the present invention is to provide a urethane-based hot melt adhesive that exhibits superior moist heat resistance to conventional urethane-based hot melt adhesives. [Means for solving the problem]
[0006] The urethane-based hot melt adhesive according to the present invention contains at least (A) polyurethane, (B) isocyanate precursor, and (C) catalyst. The polyurethane is composed of at least (a1) isocyanate-derived units having aromatic units and (a2) polyol-derived units having aromatic units. The polyurethane (A) has a hydroxyl group at its terminal. The isocyanate precursor (B) has an aromatic unit. The isocyanate precursor (B) here is, for example, a masked isocyanate, a blocked isocyanate, an isocyanate polymer, or the like.
[0007] As a result of the intensive research of the present inventors, it has become clear that the urethane-based hot melt adhesive having the above-mentioned components exhibits better resistance to moist heat than conventional urethane-based hot melt adhesives, and can maintain better adhesion than conventional urethane-based hot melt adhesives in high temperature and high humidity environments. It has also become clear that this urethane-based hot melt adhesive can maintain better adhesion than conventional urethane-based hot melt adhesives even in high temperature and high humidity environments. It has also become clear that this urethane-based hot melt adhesive develops adhesive strength in a relatively short time.
[0008] In the above-mentioned urethane-based hot melt adhesive, the isocyanate-derived unit is preferably a unit derived from at least one compound selected from the group consisting of toluene diisocyanate, diphenylmethane diisocyanate, and polymeric diphenylmethane diisocyanate, because the above-mentioned isocyanate compounds have high cohesive strength and are cost-effective.
[0009] In the above-mentioned urethane-based hot melt adhesive, the polyol-derived units are preferably units derived from a polyester polyol composed of at least carboxylic acid-derived units and polyol-derived units, and in this case, it is preferable that the carboxylic acid-derived units contain the above-mentioned aromatic units.
[0010] In the above-mentioned urethane-based hot melt adhesive, it is preferable that the polyurethane has a crosslinked structure, since this can suppress cohesive failure during curing and improve creep properties.
[0011] In the above-mentioned urethane-based hot melt adhesive, the catalyst preferably occupies a range of 0.005% by mass or more and less than 0.08% by mass of the total amount, because the adhesive cures sufficiently in an appropriate time, has a good set time, can be bonded without problems, and can prevent defects from occurring in the adhesive, thereby maintaining good strength.
[0012] In the above-mentioned urethane-based hot melt adhesive, the isocyanate precursor preferably occupies a range of 1% by mass to 15% by mass based on the total amount, because this not only increases the tensile shear adhesive strength of the urethane-based hot melt adhesive according to the present invention but also improves the moist heat resistance.
[0013] The above-mentioned urethane-based hot melt adhesive preferably further contains a silane coupling agent, because this can improve the adhesiveness to members such as glass and metal.
[0014] In the above-mentioned urethane-based hot melt adhesive, the number average molecular weight of the polyurethane is preferably within the range of 6,000 to 12,000, because this can impart good melting properties to the urethane-based hot melt adhesive according to the present invention without causing tack.
[0015] In addition, the above-mentioned urethane-based hot melt adhesive preferably has a tensile shear adhesive strength in normal state to SPCC steel plate of 5 MPa or more. Moreover, this tensile shear adhesive strength in normal state is more preferably 9 MPa or more, even more preferably 11 MPa or more, even more preferably 12 MPa or more, and particularly preferably 13 MPa or more. This is because the urethane-based hot melt adhesive according to the present invention can withstand practical use. The higher the tensile shear adhesive strength of the urethane-based hot melt adhesive to SPCC steel plate, the more preferable it is, and there is no particular upper limit. However, the adhesive strength experimentally obtained is 14 MPa or less.
[0016] In addition, in the above-mentioned urethane-based hot melt adhesive, after 500 hours of exposure to a temperature environment of 80°C (relative humidity: about 5% RH), the tensile shear bond strength to an SPCC steel plate is preferably maintained at 80% or more of the tensile shear bond strength before exposure. Moreover, this tensile shear bond strength is more preferably maintained at 90% or more of the tensile shear bond strength before exposure, and even more preferably maintained at 100%. This is because the urethane-based hot melt adhesive according to the present invention can withstand practical use even in a high-temperature environment.
[0017] In addition, in the above-mentioned urethane-based hot melt adhesive, after 500 hours of exposure to a temperature and humidity environment of 80°C and 90% RH, the tensile shear bond strength to an SPCC steel plate is preferably maintained at 80% or more of the tensile shear bond strength before exposure. Moreover, this tensile shear bond strength is more preferably maintained at 90% or more of the tensile shear bond strength before exposure, and even more preferably maintained at 100%. This is because the urethane-based hot melt adhesive according to the present invention can withstand practical use even in a high-temperature and high-humidity environment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] <Components of urethane-based hot melt adhesives> The urethane-based hot melt adhesive according to the embodiment of the present invention contains polyurethane, an isocyanate precursor, and a catalyst. In addition, this urethane-based hot melt adhesive may contain an adhesion promoter such as a silane coupling agent for the purpose of improving adhesion to members such as glass and metal, or may contain known additives for other purposes. Each of the above components will be described in detail below.
[0019] (1) Polyurethane The polyurethane is composed of at least "aromatic unit-containing isocyanate-derived units" and "aromatic unit-containing polyol-derived units". This polyurethane has a hydroxyl group at its terminal. In other words, this polyurethane can also be called a macromonomer.
[0020] Here, examples of the unit derived from an isocyanate having an aromatic unit include a unit derived from a diisocyanate having an aromatic unit. Examples of diisocyanate-derived units having an aromatic unit include toluene diisocyanate (TDI), diphenylmethane-4,4'-diisocyanate (4,4'-MDI), diphenylmethane-2,4'-diisocyanate (2,4'-MDI), polymeric diphenylmethane diisocyanate, xylene diisocyanate (XDI), 1,5-naphthalene diisocyanate (NDI), 3,3'-dimethyl-4,4'-diphenylmethane diisocyanate, O-tolidine diisocyanate, 1,4-diphenyl diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, dialkyl diphenylmethane diisocyanate, tetraalkyl diphenylmethane diisocyanate, and α,α,α,α-tetramethyl xylylene diisocyanate. In this case, the diisocyanate-derived unit having an aromatic unit is preferably a unit derived from at least one compound selected from the group consisting of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI) and polymeric diphenylmethane diisocyanate.
[0021] Toluene diisocyanate (TDI) is sold by Tosoh Corporation as, for example, Coronate T-80, Coronate T-65, and Coronate T-100. Here, Coronate T-80 is a product with a 2,4-TDI / 2,6-TDI isomer mixing ratio of 80 / 20, Coronate T-65 is a product with a 2,4-TDI / 2,6-TDI isomer ratio of 65 / 35, and Coronate T-100 is 2,4-TDI. Diphenylmethane diisocyanate (MDI) is sold by Tosoh Corporation as, for example, Millionate MT, MT-F, MTNBP, and NM. Polymeric diphenylmethane diisocyanate is sold by Tosoh Corporation as, for example, Millionate MR-100, MR-200, and MR-400.
[0022] In addition, this polyurethane may contain "isocyanate-derived units having no aromatic units" within the scope of the present invention. Examples of such isocyanate-derived units include aliphatic diisocyanates such as methylene diisocyanate, ethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (HDI), 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, lysine diisocyanate (LDI), 2-methylpentane-1,5-diisocyanate, and 3-methylpentane-1,5-diisocyanate. Examples of such diisocyanates include anate-derived units, alicyclic diisocyanates such as isophorone dicyanate (IPDI), 4,4'-dicyclohexylmethane diisocyanate (hydrogenated MDI), 1,4-cyclohexane diisocyanate, methylcyclohexylene diisocyanate (hydrogenated TDI), 1,3-bis(isocyanatomethyl)cyclohexane, and norbornene diisocyanate (NBDI), and polyisocyanate prepolymers in which an excess amount of diisocyanate is reacted with a polyol.
[0023] Examples of "polyol-derived units having aromatic units" include polyester polyols and polymer polyols, among which polyester polyols are particularly preferred. It is also preferred that the carboxylic acid-derived units in the polyester polyol contain aromatic units. Examples of such polyester polyols include polyester polyols containing units derived from isophthalic acid (IPA) or terephthalic acid (TPA), among which polyester polyols mainly composed of units derived from terephthalic acid and units derived from 3-methyl-1,5-pentanediol (MPD) are preferred. Such MPD / TPA-based polyester polyols are sold by Kuraray Co., Ltd. as, for example, Kuraray Polyol P-520, Kuraray Polyol P-1020, and Kuraray Polyol P-2020.
[0024] In addition, this polyurethane may contain "polyol-derived units having no aromatic units" within the scope of the present invention. Examples of such polyol-derived units include units derived from aliphatic diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, 1,8-octanediol, 1,9-nonanediol, diethylene glycol, dipropylene glycol, 1,4-cyclohexanedimethanol, and sorbitol ring diol, and units derived from aliphatic polyols such as poly(styrene allyl alcohol), trimethylolpropane, glycerin, pentaerythritol, and polyoxypropylenetriol. In addition, when it is necessary to introduce a crosslinked structure into this polyurethane, a multifunctional polyol is necessarily selected.
[0025] In addition, this urethane-based hot melt adhesive may contain a hydroxyl group-containing compound other than hydroxyl group-terminated urethane in addition to polyurethane, as long as the gist of the present invention is not impaired. Examples of such polyol-derived units include units derived from aliphatic diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, 1,8-octanediol, 1,9-nonanediol, diethylene glycol, dipropylene glycol, 1,4-cyclohexanedimethanol, and sorbitol ring diol, and units derived from aliphatic polyols such as poly(styrene allyl alcohol), trimethylolpropane, glycerin, pentaerythritol, and polyoxypropylenetriol.
[0026] Furthermore, the number average molecular weight of this polyurethane is preferably in the range of 6,000 or more and 12,000 or less, more preferably in the range of 7,000 or more and 12,000 or less, even more preferably in the range of 7,500 or more and 12,000 or less, even more preferably in the range of 8,000 or more and 12,000 or less, even more preferably in the range of 8,500 or more and 12,000 or less, and particularly preferably in the range of 9,000 or more and 12,000 or less.
[0027] (2) Isocyanate precursor The isocyanate precursor is, for example, a masked isocyanate (also called a "blocked isocyanate"), an isocyanate polymer (an isocyanate dimer, etc.), etc. In addition, this isocyanate precursor has an aromatic unit.
[0028] Here, the masked isocyanate having an aromatic unit is commercially available from Meisei Chemical Industry Co., Ltd. under the names of, for example, DM-6400 (MDI-based), Meikanate DM-3031CONC (MDI-based), Meikanate DM-350Z (MDI-based), and Meikanate TP-10 (TDI-based).
[0029] Examples of isocyanate multimers having an aromatic unit include toluene diisocyanate dimer and diphenylmethane diisocyanate dimer. Toluene diisocyanate dimer is sold by RheinChemie under the name Addolink (registered trademark) TT. Diphenylmethane diisocyanate dimer can be produced by the method disclosed in JP2014-097983A, for example.
[0030] In the urethane-based hot melt adhesive according to the embodiment of the present invention, the isocyanate precursor preferably occupies a range of 1% by mass to 15% by mass based on the total amount.
[0031] (3) Catalyst The catalyst plays a role in lowering the temperature at which a reaction occurs to generate an isocyanate from an isocyanate precursor, and also plays a role in reacting a polyol with an isocyanate after the generation of the isocyanate. Examples of such catalysts include tin-based catalysts such as dibutyltin dilaurate, dioctyltin dilaurate, and stannous octoate, triethylenediamine, triethylamine, N,N,N',N'-tetramethylpropylenediamine, N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine, N-methylmorpholine, 1,2-dimethylimidazole, 1,5-diazabicyclo(4,3,0)nonene-5 (hereinafter abbreviated as DBN), 1,8-diazabicyclo(4,3,0)nonene-5 (hereinafter abbreviated as DBN), and 1,8-diazabicyclo(4,3,0)nonene-5 (hereinafter abbreviated as DBN). Examples of the catalyst include (5,4,0)-undecene-7 (hereinafter abbreviated as DBU), borane salt of amine catalyst, various amine salt catalysts such as DBU phenol salt, DBU octylate, DBU formate, DBU carbonate, DBN octylate, etc., carboxylates such as magnesium naphthenate, lead naphthenate, potassium acetate, etc., trialkylphosphines such as triethylphosphine, tribenzylphosphine, etc., alkali metal alkoxides such as sodium methoxide, zinc-based organometallic catalysts, etc. Among these, DBN and DBU and their salts are preferred, and DBU formate is particularly preferred. DBU formate is sold by San-Apro Co., Ltd. under the name U-CAT SA (registered trademark) 603.
[0032] In the urethane-based hot melt adhesive according to the embodiment of the present invention, the catalyst is preferably present in an amount ranging from 0.005% by mass to less than 0.08% by mass relative to the total amount. This range of catalyst addition amount is particularly effective when 1,8-diazabicyclo(5,4,0)-undecene-7-formate is used as the catalyst.
[0033] (4) Adhesion promoter As described above, the adhesion promoter is a component that can be added arbitrarily for the purpose of improving adhesion to members such as glass, and is not particularly limited as long as it satisfactorily bonds polyurethane to members such as glass, metal, etc. Examples of the adhesion promoter include coupling agents such as silane coupling agents, titanate coupling agents, and aluminate coupling agents. Examples of the silane coupling agent include aminosilanes such as γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β(aminoethyl)-γ-aminopropyltrimethyldimethoxysilane, and N-phenyl-γ-aminopropyltrimethoxysilane; epoxysilanes such as β-(3,4-epoxycyclohexyl)-ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-glycidoxypropyltriethoxysilane; vinylsilanes such as vinyltris(β-methoxyethoxy)silane, vinyltriethoxysilane, vinyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane; hexamethyldisilazane, γ-mercaptopropyltrimethoxysilane, etc. Examples of specific silane coupling agents include Silquest A-187J from MOMENTIVE.
[0034] (5) Additives Examples of the additives include known additives such as stabilizers, fillers, curing agents, curing accelerators, plasticizers, thixotropic agents, pigments, and antioxidants.
[0035] <Manufacturing method of urethane-based hot melt adhesive> The urethane-based hot melt adhesive according to the embodiment of the present invention can be produced, for example, by the following method.
[0036] The polyurethane described above is kneaded in a kneading device in a temperature environment of 80°C to 100°C, while an isocyanate precursor and a catalyst (and additives, if necessary) are added and kneading is continued, and then the mixture is quickly cooled to room temperature, and the cooled mixture is then powdered in a grinder, and the powder is tableted in a tablet press to obtain the polyurethane.
[0037] <Properties of urethane-based hot melt adhesives> The urethane-based hot melt adhesive according to the embodiment of the present invention exhibits better resistance to moist heat than conventional urethane-based hot melt adhesives, and can maintain better adhesion than conventional urethane-based hot melt adhesives in a high temperature and high humidity environment. Specifically, the urethane-based hot melt adhesive has a normal tensile shear bond strength to an SPCC steel plate of 5 MPa or more. The normal tensile shear bond strength is more preferably 9 MPa or more, more preferably 11 MPa or more, even more preferably 12 MPa or more, and particularly preferably 13 MPa or more. The urethane-based hot melt adhesive maintains a tensile shear bond strength to an SPCC steel plate of 80% or more of the tensile shear bond strength before exposure even after 500 hours of exposure to a temperature environment of 80°C (relative humidity: about 5% RH). The urethane-based hot melt adhesive maintains a tensile shear bond strength to an SPCC steel plate of 80% or more of the tensile shear bond strength before exposure even after 500 hours of exposure to a temperature and humidity environment of 80°C and 90% RH.
[0038] The urethane hot melt adhesive according to the embodiment of the present invention has a normal tensile shear bond strength of 5 MPa or more to SPCC steel plate and exhibits a good set time. Some of these urethane hot melt adhesives have a tensile shear bond strength of more than 12 MPa under normal conditions, a tensile shear bond strength of more than 17 MPa in a temperature environment of 80°C (relative humidity: about 5% RH), and a tensile shear bond strength of more than 11 MPa in a temperature and humidity environment of 80°C and 90% RH.
[0039] <Examples and Comparative Examples> The present invention will be described in more detail below with reference to examples and comparative examples, although the present invention is not limited to the examples shown below. EXAMPLES
[0040] 1. Preparation of urethane-based hot melt adhesive (1) Preparation of hydroxyl-terminated polyurethane 100 parts by mass of Kuraray Polyol P-1020 (Kuraray Co., Ltd.) and 2.01 parts by mass of trimethylolpropane (TMP) were put into a reaction vessel, and the contents were thoroughly heated and stirred, and then 15.95 parts by mass of Coronate T-80 (Tosoh Corporation, a product with a mixing ratio of 2,4-toluene diisocyanate / 2,6-toluene diisocyanate isomers of 80 / 20) was added to the contents, and they were reacted at 100°C for 8 hours. After 8 hours, the isocyanate value (mass ratio of remaining isocyanate groups to solid content) was 0.01% or less. That is, a polyurethane having a hydroxyl group at the end (hereinafter referred to as "hydroxyl-terminated polyurethane") was obtained. The R value of this hydroxyl-terminated polyurethane (molar ratio of isocyanate groups to hydroxyl groups) was 0.75. When the hydroxyl-terminated polyurethane was touched with a finger in a room temperature environment, no tack (stickiness) was felt. Hereinafter, this hydroxyl-terminated polyurethane may be abbreviated as "PU1."
[0041] The number average molecular weight of this hydroxyl-terminated polyurethane was measured by gel permeation chromatography under the following conditions, and was found to be 8,533 in terms of polystyrene. Measuring equipment (GPC): Shodex GPC-101 manufactured by Showa Denko K.K. Column: Shodex LF804 manufactured by Showa Denko K.K. Column temperature: 40℃ Detector: Differential refractometer (RI detector) Sample concentration: 0.2% by volume Diluent: Tetrahydrofuran ·Mobile phase flow rate: 1.0mL / min
[0042] (2) Preparation of urethane-based hot melt adhesive 93.73 parts by mass of the above-mentioned hydroxyl-terminated polyurethane (PU1) was mixed in a mixer at a temperature of about 100°C, while 5.15 parts by mass of Addolink (registered trademark) TT (TDI dimer manufactured by RheinChemie), 0.03 parts by mass of U-CAT SA (registered trademark) 603, and 1.09 parts by mass of a silane coupling agent Silquest A-187J (manufactured by MOMENTIVE) were added thereto, and the mixture was further mixed and then cooled quickly to room temperature. The cooled mixture was then powdered in a pulverizer, and the powder was tableted in a tablet press to obtain the desired urethane-based hot melt adhesive.
[0043] 2. Evaluation of the physical properties of urethane-based hot melt adhesives (1) Measurement of tensile shear adhesive strength a. Preparation of test specimens A degreased SPCC steel plate measuring 25 mm wide x 100 mm long x 1.6 mm thick was heated to 160°C in an environment of 23°C and 50% RH, and the urethane-based hot melt adhesive prepared as described above was then placed on the heated SPCC steel plate for 10 seconds. A SPCC steel plate of the same size and heated to 80°C was then placed on top of the urethane-based hot melt adhesive, overlapping by 12.5 mm. The overlapping portions of the two SPCC steel plates were secured with clips and left for 24 hours to prepare the desired test specimens.
[0044] b.Measurement method The non-overlapping portion of the SPCC steel plate of the test piece obtained as described above was fixed to two opposing chucks, and the test piece was pulled at a speed of 10 mm / min in a temperature and humidity environment of 25°C and 50 RH. The details of this measurement were in accordance with JIS K6850. As a result, the tensile shear adhesive strength of the urethane-based hot melt adhesive according to this example in the above measurement atmosphere (hereinafter referred to as "normal tensile shear adhesive strength") was 12.3 MPa.
[0045] (2) Examination of the effect of environment on tensile shear bond strength (2-1) Thermal environment of 80℃ a. Preparation of test specimens Test specimens were prepared as described in "a. Preparation of test specimens" in the section "(1) Measurement of tensile shear adhesive strength" above, and then the test specimens were placed in a dryer at 80°C for 500 hours.
[0046] b.Measurement method The tensile shear bond strength was measured as described in "b. Measurement method" in the above-mentioned section "(1) Measurement of tensile shear bond strength". The measurement atmosphere was 25°C and 50% RH. As a result, the tensile shear bond strength of the urethane-based hot melt adhesive according to this embodiment after 500 hours of exposure to a hot environment of 80°C was 14.9 MPa in the above-mentioned measurement environment. That is, the urethane-based hot melt adhesive retained 121% (=14.9 / 12.3×100) of the tensile shear bond strength before the above-mentioned exposure to the hot environment (hereinafter, this value is referred to as "tensile shear bond strength retention rate"). (That is, a 21% strength improvement was observed.)
[0047] (2-2) Hot and humid environment of 80℃ and 90% RH a. Preparation of test specimens Test specimens were prepared as described in "a. Preparation of test specimens" in the above section "(1) Measurement of tensile shear adhesive strength", and then the test specimens were placed in a thermo-hygrostat at 80°C and 90% RH for 500 hours.
[0048] b.Measurement method The tensile shear adhesive strength was measured as described in "b. Measurement method" in the above-mentioned "(1) Measurement of tensile shear adhesive strength". The measurement atmosphere was 25°C and 50% RH. As a result, the tensile shear adhesive strength of the urethane-based hot melt adhesive according to this embodiment after 500 hours of exposure to a hot, humid, and heat environment of 80°C and 90% RH in the above-mentioned measurement environment was 13.0 MPa. In other words, the urethane-based hot melt adhesive retained 106% (=13.0 / 12.3×100) of the tensile shear adhesive strength before exposure to the above-mentioned hot environment.
[0049] (3) Measurement of film properties a. Preparation of test specimens The urethane-based hot melt adhesive prepared as described above was diluted with a solvent so that the solid content was 80% by weight. The diluted solution was then applied to a release paper, and the coating film was dried at 80°C for 30 minutes and then left at 130°C for 60 minutes. The solid coating film obtained on the release paper was then peeled off from the release paper to prepare the desired test piece.
[0050] b.Measurement method The test piece obtained as described above was fixed to two opposing chucks and pulled at a speed of 200 mm / min in a temperature and humidity environment of 25°C and 50% RH. Details of this measurement were in accordance with JIS K7161. As a result, the tensile strength of the film of the urethane-based hot melt adhesive according to this example was 21.9 MPa, and the tensile elongation was 40.0%.
[0051] (4) Study of the environmental effects on film properties (4-1) Thermal environment of 80℃ a. Preparation of test specimens Test pieces were prepared as described in "a. Preparation of test pieces" in the section "(3) Measurement of film physical properties" above, and then the test pieces were placed in a dryer at 80° C. for 500 hours.
[0052] b.Measurement method The test piece was pulled as described in "b. Measurement method" in the above-mentioned "(3) Measurement of film physical properties" section, and the tensile strength and tensile elongation of the test piece were measured. The measurement atmosphere was 25°C and 50% RH. As a result, the tensile strength of the urethane-based hot melt adhesive film according to this embodiment after 500 hours of exposure to a hot environment of 80°C was 22.5 MPa and the tensile elongation was 60.0% in the above-mentioned measurement environment. That is, the urethane-based hot melt adhesive film retained 103% (=22.5 / 21.9×100) of the tensile strength before the above-mentioned exposure to the hot environment (hereinafter, this value is referred to as "film tensile strength retention rate"). (That is, a 3% strength improvement was observed.)
[0053] (4-2) Hot and humid environment of 80℃ and 90% RH a. Preparation of test specimens Test pieces were prepared as described in "a. Preparation of test pieces" in the above section "(3) Measurement of film physical properties", and then the test pieces were placed in a thermo-hygrostat at 80° C. and 90% RH for 500 hours.
[0054] b.Measurement method The test piece was pulled as described in "b. Measurement method" in the above-mentioned "(3) Measurement of film physical properties" section, and the tensile strength and tensile elongation of the test piece were measured. The measurement atmosphere was 25°C and 50% RH. As a result, the tensile strength of the urethane-based hot melt adhesive film according to this embodiment after 500 hours of exposure to a hot, humid, and hot environment of 80°C and 90% RH was 26.7 MPa and the tensile elongation was 25.0% in the above-mentioned measurement environment. That is, the urethane-based hot melt adhesive film retained 122% (=26.7 / 21.9×100) of the tensile strength before the above-mentioned exposure to the hot environment (i.e., a 22% strength improvement was observed).
[0055] (5) Measurement of set time A degreased disk-shaped SPCC steel plate with a diameter of 24 mm and a weight of 12 g was heated to 160°C in an environment of 23°C and 50% RH, and then the urethane-based hot melt adhesive prepared as described above was applied to the heated disk-shaped SPCC steel plate and left for 10 seconds. The disk-shaped SPCC steel plate was then laminated to a degreased rectangular SPCC steel plate with a width of 25 mm, a length of 100 mm, and a thickness of 1.6 mm that had been heated to 80°C. Immediately after lamination, the rectangular SPCC steel plate of the joint was held and lifted up to the joint. If the lower disk-shaped SPCC steel plate did not slip off under its own weight, it was judged to be "good", and if the disk-shaped SPCC steel plate slipped off, it was judged to be "bad". As a result, the disk-shaped SPCC steel plate did not slip off, and the set time was judged to be good.
[0056] (6) Measurement of adhesive melting properties As described in "(4) Measurement of set time" above, two SPCC steel sheets were bonded together, then peeled off to check the spread (meltability) of the adhesive on each SPCC steel sheet. If the adhesive spread easily when the SPCC steel sheets were bonded together, it was judged to be "good", and if it did not spread easily, it was judged to be "poor". As a result, this urethane-based hot melt adhesive spread easily when the SPCC steel sheets were bonded together, and it was judged to have good meltability. EXAMPLES
[0057] 1. Preparation of urethane-based hot melt adhesive (1) Preparation of hydroxyl-terminated polyurethane A hydroxyl-terminated polyurethane was obtained in the same manner as in Example 1, except that the amount of Coronate T-80 added was changed to 16.47 parts by mass, and the tackiness of the hydroxyl-terminated polyurethane was confirmed by touching with fingers at room temperature, and the polystyrene-equivalent number average molecular weight of the hydroxyl-terminated polyurethane was measured. As a result, no tack (stickiness) was felt, and the polystyrene-equivalent number average molecular weight was 8999. The R value of this hydroxyl-terminated polyurethane was 0.77. Hereinafter, this hydroxyl-terminated polyurethane may be abbreviated as "PU2".
[0058] (2) Preparation of urethane-based hot melt adhesive A urethane-based hot melt adhesive was obtained in the same manner as in Example 1, except that the amount of hydroxyl-terminated polyurethane (PU2) added was changed to 94.22 parts by mass, the amount of Addolink (registered trademark) TT added was changed to 4.65 parts by mass, and the amount of silane coupling agent Silquest A-187J added was changed to 1.10 parts by mass.
[0059] 2. Evaluation of the physical properties of urethane-based hot melt adhesives The physical properties of this urethane-based hot melt adhesive were evaluated in the same manner as in Example 1.The tensile shear bond strength of the urethane-based hot melt adhesive of this example in its normal state was 13.5 MPa, the tensile shear bond strength of the urethane-based hot melt adhesive of this example after 500 hours of exposure to an 80°C hot environment was 14.3 MPa (tensile shear bond strength retention: 106%), and the tensile shear bond strength of the urethane-based hot melt adhesive of this example after 500 hours of exposure to an 80°C, 90% RH hot, humid heat environment was 11.0 MPa (tensile shear bond strength retention: 81%). In addition, the urethane-based hot melt adhesive film according to this embodiment had a normal tensile strength of 22.3 MPa and a tensile elongation of 20.0%. After 500 hours of exposure to a 80°C hot and hot environment, the urethane-based hot melt adhesive film according to this embodiment had a tensile strength of 29.4 MPa (film tensile strength retention: 132%) and a tensile elongation of 27.0%. After 500 hours of exposure to a 80°C, 90% RH hot and humid heat environment, the urethane-based hot melt adhesive film according to this embodiment had a tensile strength of 26.2 MPa (film tensile strength retention: 117%) and a tensile elongation of 18.0%. In addition, the setting time and melting property of the urethane-based hot melt adhesive according to this embodiment were judged to be good. EXAMPLES
[0060] 1. Preparation of urethane-based hot melt adhesive (1) Preparation of hydroxyl-terminated polyurethane A hydroxyl-terminated polyurethane was obtained in the same manner as in Example 1, except that the amount of Coronate T-80 added was changed to 14.72 parts by mass, and the tackiness of the hydroxyl-terminated polyurethane was confirmed by touching with fingers at room temperature, and the number average molecular weight of the hydroxyl-terminated polyurethane was measured in terms of polystyrene. As a result, the number average molecular weight in terms of polystyrene was 6776. Furthermore, when the obtained hydroxyl-terminated polyurethane was touched with fingers, it was not felt to be tacky (sticky). Furthermore, the R value of this hydroxyl-terminated polyurethane was 0.69. Hereinafter, this hydroxyl-terminated polyurethane may be abbreviated as "PU3".
[0061] (2) Preparation of urethane-based hot melt adhesive A urethane-based hot melt adhesive was obtained in the same manner as in Example 1, except that the amount of hydroxyl-terminated polyurethane (PU3) added was changed to 92.56 parts by mass, and the amount of Addolink (registered trademark) TT added was changed to 6.32 parts by mass.
[0062] 2. Evaluation of the physical properties of urethane-based hot melt adhesives The physical properties of this urethane-based hot melt adhesive were evaluated in the same manner as in Example 1.The tensile shear bond strength of the urethane-based hot melt adhesive of this example in its normal state was 13.1 MPa, the tensile shear bond strength of the urethane-based hot melt adhesive of this example after 500 hours of exposure to an 80°C hot environment was 17.5 MPa (tensile shear bond strength retention: 134%), and the tensile shear bond strength of the urethane-based hot melt adhesive of this example after 500 hours of exposure to an 80°C, 90% RH hot, humid heat environment was 10.8 MPa (tensile shear bond strength retention: 82%). In addition, the urethane-based hot melt adhesive film according to this embodiment had a normal tensile strength of 28.2 MPa and a tensile elongation of 13.3%. After 500 hours of exposure to a 80°C hot and cold environment, the urethane-based hot melt adhesive film according to this embodiment had a tensile strength of 31.9 MPa (film tensile strength retention: 113%) and a tensile elongation of 57.0%. After 500 hours of exposure to a 80°C, 90% RH hot and humid heat environment, the urethane-based hot melt adhesive film according to this embodiment had a tensile strength of 35.2 MPa (film tensile strength retention: 125%) and a tensile elongation of 25.0%. In addition, the setting time and melting property of the urethane-based hot melt adhesive according to this embodiment were judged to be good. EXAMPLES
[0063] 1. Preparation of urethane-based hot melt adhesive (1) Preparation of hydroxyl-terminated polyurethane A hydroxyl-terminated polyurethane was obtained in the same manner as in Example 1, except that the amount of Coronate T-80 added was changed to 13.94 parts by mass, and the tackiness of the hydroxyl-terminated polyurethane was confirmed by touching with fingers at room temperature, and the polystyrene-equivalent number average molecular weight of the hydroxyl-terminated polyurethane was measured. As a result, no tack (stickiness) was felt, and the polystyrene-equivalent number average molecular weight was 6375. The R value of this hydroxyl-terminated polyurethane was 0.65. Hereinafter, this hydroxyl-terminated polyurethane may be abbreviated as "PU4".
[0064] (2) Preparation of urethane-based hot melt adhesive A urethane-based hot melt adhesive was obtained in the same manner as in Example 1, except that the amount of hydroxyl-terminated polyurethane (PU4) added was changed to 91.86 parts by mass, the amount of Addolink (registered trademark) TT added was changed to 7.04 parts by mass, and the amount of silane coupling agent Silquest A-187J added was changed to 1.07 parts by mass.
[0065] 2. Evaluation of the physical properties of urethane-based hot melt adhesives The physical properties of this urethane-based hot melt adhesive were evaluated in the same manner as in Example 1.The tensile shear bond strength of the urethane-based hot melt adhesive of this example in its normal state was 11.0 MPa, the tensile shear bond strength of the urethane-based hot melt adhesive of this example after 500 hours of exposure to an 80°C hot environment was 14.9 MPa (tensile shear bond strength retention: 128%), and the tensile shear bond strength of the urethane-based hot melt adhesive of this example after 500 hours of exposure to an 80°C, 90% RH hot, humid heat environment was 8.9 MPa (tensile shear bond strength retention: 81%). In addition, the urethane-based hot melt adhesive film according to this embodiment had a normal tensile strength of 31.4 MPa and a tensile elongation of 30.0%, and after 500 hours of exposure to a 80°C hot and hot environment, the urethane-based hot melt adhesive film according to this embodiment had a tensile strength of 25.2 MPa (film tensile strength retention rate: 80%) and a tensile elongation of 38.0%, and after 500 hours of exposure to a 80°C, 90% RH hot and humid heat environment, the urethane-based hot melt adhesive film according to this embodiment had a tensile strength of 29.6 MPa (film tensile strength retention rate: 94%) and a tensile elongation of 15.0%. In addition, the setting time and melting property of the urethane-based hot melt adhesive according to this embodiment were judged to be good. EXAMPLES
[0066] 1. Preparation of urethane-based hot melt adhesive (1) Preparation of hydroxyl-terminated polyurethane A hydroxyl-terminated polyurethane was obtained in the same manner as in Example 1, except that 15.95 parts by mass of Coronate T-80 was replaced with 22.88 parts by mass of Millionate MT (manufactured by Mitsui Chemicals, Inc., monomeric MDI (diphenylmethane diisocyanate), pure MDI, molecular weight 250). The tackiness of the hydroxyl-terminated polyurethane was confirmed by touching with fingers at room temperature, and the polystyrene-equivalent number average molecular weight of the hydroxyl-terminated polyurethane was measured. As a result, no tackiness (stickiness) was felt, and the polystyrene-equivalent number average molecular weight was 11059. The R value of this hydroxyl-terminated polyurethane was 0.75. Hereinafter, this hydroxyl-terminated polyurethane may be abbreviated as "PU5".
[0067] (2) Preparation of urethane-based hot melt adhesive A urethane-based hot melt adhesive was obtained in the same manner as in Example 1, except that the amount of hydroxyl-terminated polyurethane (PU5) added was changed to 94.01 parts by mass, the amount of Addolink (registered trademark) TT added was changed to 4.86 parts by mass, and the amount of silane coupling agent Silquest A-187J added was changed to 1.10 parts by mass. 2. Evaluation of the physical properties of urethane-based hot melt adhesives The physical properties of this urethane-based hot melt adhesive were evaluated in the same manner as in Example 1.The tensile shear bond strength of the urethane-based hot melt adhesive of this example in its normal state was 12.0 MPa, the tensile shear bond strength of the urethane-based hot melt adhesive of this example after 500 hours of exposure to an 80°C hot environment was 13.8 MPa (tensile shear bond strength retention: 115%), and the tensile shear bond strength of the urethane-based hot melt adhesive of this example after 500 hours of exposure to an 80°C, 90% RH hot, humid heat environment was 11.8 MPa (tensile shear bond strength retention: 98%). In addition, the urethane-based hot melt adhesive film according to this embodiment had a normal tensile strength of 19.8 MPa and a tensile elongation of 45.0%, and after 500 hours of exposure to a 80°C hot and hot environment, the urethane-based hot melt adhesive film according to this embodiment had a tensile strength of 23.0 MPa (film tensile strength retention: 116%) and a tensile elongation of 40.0%, and after 500 hours of exposure to a 80°C, 90% RH hot and humid heat environment, the urethane-based hot melt adhesive film according to this embodiment had a tensile strength of 23.5 MPa (film tensile strength retention: 119%) and a tensile elongation of 38.0%. In addition, the setting time and melting property of the urethane-based hot melt adhesive according to this embodiment were judged to be good. EXAMPLES
[0068] 1. Preparation of urethane-based hot melt adhesive (1) Preparation of hydroxyl-terminated polyurethane In the same manner as in Example 1, a hydroxyl-terminated polyurethane (PU1) was obtained.
[0069] (2) Preparation of urethane-based hot melt adhesive A urethane-based hot melt adhesive was obtained in the same manner as in Example 1, except that the amount of hydroxyl-terminated polyurethane (PU1) added was changed to 93.70 parts by mass, and the amount of U-CAT SA (registered trademark) 603 added was changed to 0.06 parts by mass. 2. Evaluation of the physical properties of urethane-based hot melt adhesives The physical properties of this urethane-based hot melt adhesive were evaluated in the same manner as in Example 1. The tensile shear adhesive strength of the urethane-based hot melt adhesive according to this example was 9.6 MPa in normal state, the tensile shear adhesive strength of the urethane-based hot melt adhesive according to this example after 500 hours of exposure to a 80°C hot and hot environment was 11.3 MPa (tensile shear adhesive strength retention rate: 118%), and the tensile shear adhesive strength of the urethane-based hot melt adhesive according to this example after 500 hours of exposure to a 80°C, 90% RH hot and humid heat environment was 10.1 MPa (tensile shear adhesive strength retention rate: 105%). In addition, the tensile strength of the urethane-based hot melt adhesive film according to this example in normal state was 22.0 MPa, and the tensile elongation was 35.0%. In addition, the setting time and melting property of the urethane-based hot melt adhesive according to this example were judged to be good. EXAMPLES
[0070] 1. Preparation of urethane-based hot melt adhesive (1) Preparation of hydroxyl-terminated polyurethane In the same manner as in Example 1, a hydroxyl-terminated polyurethane (PU1) was obtained.
[0071] (2) Preparation of urethane-based hot melt adhesive A urethane-based hot melt adhesive was obtained in the same manner as in Example 1, except that the amount of hydroxyl-terminated polyurethane (PU1) added was changed to 93.74 parts by mass, the amount of Addolink (registered trademark) TT added was changed to 5.16 parts by mass, and the amount of U-CAT SA (registered trademark) 603 added was changed to 0.01 parts by mass.
[0072] 2. Evaluation of the physical properties of urethane-based hot melt adhesives The physical properties of this urethane-based hot melt adhesive were evaluated in the same manner as in Example 1. The tensile shear adhesive strength of the urethane-based hot melt adhesive according to this example was 14.2 MPa in normal state, the tensile shear adhesive strength of the urethane-based hot melt adhesive according to this example after 500 hours of exposure to a 80°C hot and hot environment was 14.7 MPa (tensile shear adhesive strength retention rate: 103%), and the tensile shear adhesive strength of the urethane-based hot melt adhesive according to this example after 500 hours of exposure to a 80°C, 90% RH hot and humid heat environment was 12.8 MPa (tensile shear adhesive strength retention rate: 90%). In addition, the tensile strength of the urethane-based hot melt adhesive film according to this example in normal state was 20.3 MPa, and the tensile elongation was 30.0%. In addition, the setting time and melting property of the urethane-based hot melt adhesive according to this example were judged to be good. EXAMPLES
[0073] 1. Preparation of urethane-based hot melt adhesive (1) Preparation of hydroxyl-terminated polyurethane In the same manner as in Example 1, a hydroxyl-terminated polyurethane (PU1) was obtained.
[0074] (2) Preparation of urethane-based hot melt adhesive A urethane-based hot melt adhesive was obtained in the same manner as in Example 1, except that the amount of hydroxyl-terminated polyurethane (PU1) added was changed to 88.63 parts by mass, the amount of Addolink (registered trademark) TT added was changed to 10.04 parts by mass, the amount of silane coupling agent Silquest A-187J added was changed to 1.03 parts by mass, and 0.03 parts by mass of U-CAT SA (registered trademark) 603 was replaced by 0.30 parts by mass of 1,5-diazabicyclo(4,3,0)nonene-5 (DBN, manufactured by San-Apro Co., Ltd.).
[0075] 2. Evaluation of the curing reaction of urethane-based hot melt adhesive The urethane-based hot melt adhesive obtained as described above was packed into an aluminum sample pan to prepare a sample. A control was also prepared from the same aluminum sample pan. The sample and control were set in a differential scanning calorimeter (DSC8230, manufactured by Rigaku Corporation), and the sample and control were heated from room temperature to 250°C at a rate of 10°C / min while the change in heat was measured. As a result, it was found that this urethane-based hot melt adhesive had a reaction range of 80.8°C-131.4°C (peak temperature: 117.8°C). EXAMPLES
[0076] 1. Preparation of urethane-based hot melt adhesive (1) Preparation of hydroxyl-terminated polyurethane In the same manner as in Example 1, a hydroxyl-terminated polyurethane (PU1) was obtained.
[0077] (2) Preparation of urethane-based hot melt adhesive A urethane-based hot melt adhesive was obtained in the same manner as in Example 1, except that the amount of hydroxyl-terminated polyurethane (PU1) added was changed to 88.63 parts by mass, the amount of Addolink (registered trademark) TT added was changed to 10.04 parts by mass, the amount of silane coupling agent Silquest A-187J added was changed to 1.03 parts by mass, and 0.03 parts by mass of U-CAT SA (registered trademark) 603 was replaced by 0.30 parts by mass of U-Cat SA (registered trademark) 1 (DBU phenol salt, manufactured by San-Apro Co., Ltd.).
[0078] 2. Evaluation of the curing reaction of urethane-based hot melt adhesive The urethane-based hot melt adhesive obtained as described above was packed into an aluminum sample pan to prepare a sample. A control was also prepared from the same aluminum sample pan. The sample and the control were set in a differential scanning calorimeter (DSC8230, manufactured by Rigaku Denki Co., Ltd.), and the heat change was measured while the sample and the control were heated from room temperature to 250°C at a rate of 10°C / min. As a result, it was found that this urethane-based hot melt adhesive had a reaction range of 94.8°C-148.1°C (peak temperature: 132.5°C). EXAMPLES
[0079] 1. Preparation of urethane-based hot melt adhesive (1) Preparation of hydroxyl-terminated polyurethane In the same manner as in Example 1, a hydroxyl-terminated polyurethane (PU1) was obtained.
[0080] (2) Preparation of urethane-based hot melt adhesive A urethane-based hot melt adhesive was obtained in the same manner as in Example 1, except that the amount of hydroxyl-terminated polyurethane (PU1) added was changed to 88.63 parts by mass, the amount of Addolink (registered trademark) TT added was changed to 10.04 parts by mass, the amount of silane coupling agent Silquest A-187J added was changed to 1.03 parts by mass, and 0.03 parts by mass of U-CAT SA (registered trademark) 603 was replaced by 0.30 parts by mass of U-Cat SA (registered trademark) 102 (DBU octyl salt, manufactured by San-Apro Co., Ltd.).
[0081] 2. Evaluation of the curing reaction of urethane-based hot melt adhesive The urethane-based hot melt adhesive obtained as described above was packed into an aluminum sample pan to prepare a sample. A control was also prepared from the same aluminum sample pan. The sample and the control were set in a differential scanning calorimeter (DSC8230, manufactured by Rigaku Denki Co., Ltd.), and the change in heat was measured while the sample and the control were heated from room temperature to 250°C at a rate of 10°C / min. As a result, it was found that this urethane-based hot melt adhesive had a reaction range of 94.9°C-153.3°C (peak temperature: 140.5°C). EXAMPLES
[0082] 1. Preparation of urethane-based hot melt adhesive (1) Preparation of hydroxyl-terminated polyurethane In the same manner as in Example 1, a hydroxyl-terminated polyurethane (PU1) was obtained.
[0083] (2) Preparation of urethane-based hot melt adhesive A urethane-based hot melt adhesive was obtained in the same manner as in Example 1, except that the amount of hydroxyl-terminated polyurethane (PU1) added was changed to 88.63 parts by mass, the amount of Addolink (registered trademark) TT added was changed to 10.04 parts by mass, the amount of silane coupling agent Silquest A-187J added was changed to 1.03 parts by mass, and the amount of U-CAT SA (registered trademark) 603 added was changed to 0.30 parts by mass.
[0084] 2. Evaluation of the curing reaction of urethane-based hot melt adhesive The urethane-based hot melt adhesive obtained as described above was packed into an aluminum sample pan to prepare a sample. A control was also prepared from the same aluminum sample pan. The sample and control were set in a differential scanning calorimeter (DSC8230, manufactured by Rigaku Corporation), and the heat change was measured while the sample and control were heated from room temperature to 250°C at a rate of 10°C / min. As a result, it was found that this urethane-based hot melt adhesive had a reaction range of 73.1°C-150.4°C (peak temperature: 139.2°C).
[0085] Comparative Example 1 1. Preparation of urethane-based hot melt adhesive (1) Preparation of hydroxyl-terminated polyurethane A hydroxyl-terminated polyurethane was obtained in the same manner as in Example 1, except that Kuraray Polyol P-1020 was replaced with Diol-1000 (manufactured by Mitsui Chemicals SKC Polyurethanes, Inc., polypropylene glycol, molecular weight 1,000), and the tackiness of the hydroxyl-terminated polyurethane was confirmed by touching with fingers at room temperature. As a result, the hydroxyl-terminated polyurethane was liquid and felt tacky (sticky). The R value of this hydroxyl-terminated polyurethane was 0.75. Hereinafter, this hydroxyl-terminated polyurethane may be abbreviated as "PU6".
[0086] (2) Preparation of urethane-based hot melt adhesive A urethane-based hot melt adhesive was obtained in the same manner as in Example 1 (except that PU6 hydroxyl-terminated polyurethane was used as the hydroxyl-terminated polyurethane).
[0087] The physical properties of this urethane-based hot melt adhesive were evaluated in the same manner as in Example 1.The tensile shear adhesive strength of the urethane-based hot melt adhesive of this comparative example in its normal state was 0.58 MPa, the tensile shear adhesive strength of the urethane-based hot melt adhesive of this comparative example after 500 hours of exposure to an 80°C hot and humid heat environment was 0.74 MPa (retention rate: 127%), and the tensile shear adhesive strength of the urethane-based hot melt adhesive of this comparative example after 500 hours of exposure to an 80°C, 90% RH hot and humid heat environment was 1.40 MPa (retention rate: 241%). The urethane-based hot melt adhesive film according to this comparative example had a normal tensile strength of 0.57 MPa and a tensile elongation of 410%, and after 500 hours of exposure to a 80°C hot and hot environment, the urethane-based hot melt adhesive film according to this comparative example had a tensile strength of 0.44 MPa (film tensile strength retention: 77%) and a tensile elongation of 350%, and after 500 hours of exposure to a 80°C, 90% RH hot and humid heat environment, the urethane-based hot melt adhesive film according to this comparative example had a tensile strength of 0.34 MPa (film tensile strength retention: 59%) and a tensile elongation of 300%. The set time and meltability of the urethane-based hot melt adhesive according to this comparative example were also determined to be poor.
[0088] Comparative Example 2 1. Preparation of urethane-based hot melt adhesive (1) Preparation of hydroxyl-terminated polyurethane A hydroxyl-terminated polyurethane was obtained in the same manner as in Example 1, except that Kuraray Polyol P-1020 was replaced with Nipporan 981 (aliphatic polycarbonate diol, manufactured by Tosoh Corporation), and the tackiness of the hydroxyl-terminated polyurethane was checked by touching with fingers at room temperature. As a result, no tackiness (stickiness) was felt. The R value of this hydroxyl-terminated polyurethane was 0.75. Hereinafter, this hydroxyl-terminated polyurethane may be abbreviated as "PU7".
[0089] (2) Preparation of urethane-based hot melt adhesive A urethane-based hot melt adhesive was obtained in the same manner as in Example 1 (except that PU7 hydroxyl-terminated polyurethane was used as the hydroxyl-terminated polyurethane).
[0090] The physical properties of this urethane-based hot melt adhesive were evaluated in the same manner as in Example 1. The tensile shear adhesive strength of the urethane-based hot melt adhesive of this comparative example in its normal state was 1.34 MPa, the tensile shear adhesive strength of the urethane-based hot melt adhesive of this comparative example after 500 hours of exposure to an 80°C hot environment was 3.37 MPa (retention rate: 251%), and the tensile shear adhesive strength of the urethane-based hot melt adhesive of this comparative example after 500 hours of exposure to an 80°C, 90% RH hot, humid heat environment was 3.30 MPa (retention rate: 246%). The urethane-based hot melt adhesive film according to this comparative example had a normal tensile strength of 9.61 MPa and a tensile elongation of 322%, and after 500 hours of exposure to a 80°C hot and hot environment, the urethane-based hot melt adhesive film according to this comparative example had a tensile strength of 7.9 MPa (film tensile strength retention: 82%) and a tensile elongation of 355%, and after 500 hours of exposure to a 80°C, 90% RH hot and humid heat environment, the urethane-based hot melt adhesive film according to this comparative example had a tensile strength of 8.5 MPa (film tensile strength retention: 88%) and a tensile elongation of 408%. The set time and meltability of the urethane-based hot melt adhesive according to this comparative example were also determined to be poor.
[0091] Comparative Example 3 1. Preparation of urethane-based hot melt adhesive (1) Preparation of hydroxyl-terminated polyurethane A hydroxyl-terminated polyurethane was obtained in the same manner as in Example 1, except that Kuraray Polyol P-1020 was replaced with Kuraray Polyol P-1010 (aliphatic polyester polyol synthesized from adipic acid and 3-methyl-1,5-pentanediol, manufactured by Kuraray Co., Ltd.), and the tackiness of the hydroxyl-terminated polyurethane was confirmed by touching with fingers at room temperature. As a result, the hydroxyl-terminated polyurethane was liquid and felt tacky (sticky). The R value of this hydroxyl-terminated polyurethane was 0.75. Hereinafter, this hydroxyl-terminated polyurethane may be abbreviated as "PU8".
[0092] (2) Preparation of urethane-based hot melt adhesive A urethane-based hot melt adhesive was obtained in the same manner as in Example 1 (except that PU8 hydroxyl-terminated polyurethane was used as the hydroxyl-terminated polyurethane).
[0093] The physical properties of this urethane-based hot melt adhesive were evaluated in the same manner as in Example 1. The tensile shear adhesive strength of the urethane-based hot melt adhesive of this comparative example in its normal state was 1.48 MPa, the tensile shear adhesive strength of the urethane-based hot melt adhesive of this comparative example after 500 hours of exposure to an 80°C hot and humid environment was 1.62 MPa (retention rate: 109%), and the tensile shear adhesive strength of the urethane-based hot melt adhesive of this comparative example after 500 hours of exposure to an 80°C, 90% RH hot and humid heat environment was 1.14 MPa (retention rate: 77%). The urethane-based hot melt adhesive film according to this comparative example had a normal tensile strength of 2.14 MPa and a tensile elongation of 345%, and after 500 hours of exposure to a 80°C hot and hot environment, the urethane-based hot melt adhesive film according to this comparative example had a tensile strength of 1.68 MPa (film tensile strength retention: 78%) and a tensile elongation of 327%, and after 500 hours of exposure to a 80°C, 90% RH hot and humid heat environment, the urethane-based hot melt adhesive film according to this comparative example had a tensile strength of 1.29 MPa (film tensile strength retention: 60%) and a tensile elongation of 645%. The set time and meltability of the urethane-based hot melt adhesive according to this comparative example were also determined to be poor.
[0094] (summary) The raw material compositions and physical properties of the products prepared in the above Examples and Comparative Examples are summarized in Tables 1 to 4 below. The raw material composition, R value, number average molecular weight, and tackiness of the hydroxyl-terminated polyurethanes prepared in each of the Examples and Comparative Examples are summarized in Table 1. As is clear from Table 1, the hydroxyl-terminated polyurethanes of the Examples did not have tackiness, but the hydroxyl-terminated polyurethanes of the Comparative Examples except Comparative Example 2 did have tackiness.
[0095] Table 2 summarizes the raw material compositions of the urethane-based hot melt adhesives prepared in Examples 1 to 5 and Comparative Examples 1 to 3, as well as their set times, spread (meltability), and tensile shear adhesive strength and film properties in various environments. As is clear from Table 2, the urethane-based hot melt adhesives according to the Examples have good set times and spread (meltability), while the urethane-based hot melt adhesives according to the Comparative Examples have poor set times and spread (meltability). Also, as is clear from Table 2, the urethane-based hot melt adhesives according to the Examples exhibit stable adhesive properties and film properties in any environment, while the urethane-based hot melt adhesives according to the Comparative Examples have unstable adhesive properties and film properties in high temperature environments or high temperature and high humidity environments.
[0096] Table 3 summarizes the raw material compositions and cured physical properties of the urethane hot melt adhesives prepared in Examples 8 to 11. As is clear from Table 3, the urethane hot melt adhesives cure well with any catalyst, but in consideration of reducing the waste of thermal energy and improving the workability of laminating adherends, U-Cat SA603 of Example 11, which begins to cure at a relatively low temperature and completes curing at a relatively high temperature, is particularly desirable.
[0097] Table 4 summarizes the raw material compositions of the urethane hot melt adhesives prepared in Examples 1, 6, and 7, as well as their set times, spread (meltability), tensile shear adhesive strengths in various environments, and film properties. As is clear from Table 4, the urethane hot melt adhesives cure well if about 0.01% by mass to 0.06% by mass of a catalyst is added.
[0098] [Table 1]
[0099] [Table 2]
[0100] [Table 3]
[0101] [Table 4] [Industrial Applicability]
[0102] The urethane-based hot melt adhesive of the present invention has the characteristics of exhibiting superior heat resistance and moist heat resistance to conventional urethane-based hot melt adhesives and developing adhesive strength in a relatively short time, and is particularly useful in hot and humid locations and regions, etc. Furthermore, such urethane-based hot melt adhesives are useful for bonding parts of vehicles (e.g., automobiles, motorcycles, trains, airplanes, ships, bicycles, etc.) that can be used in the above-mentioned regions.
Claims
1. (A) a polyurethane comprising (a1) an isocyanate-derived unit having an aromatic unit, (a2) a polyol-derived unit having an aromatic unit, and (a3) a trimethylolpropane-derived unit, and having a hydroxyl group at a terminal thereof, the molar ratio of the isocyanate group to the hydroxyl group being within the range of 0.65 or more and 0.77 or less; (B) toluene diisocyanate dimer; (C) a catalyst; Contains the polyurethane is obtained by polymerizing 100 parts by mass of the polyol having the aromatic unit, 13.94 parts by mass or more and 22.88 parts by mass or less of the isocyanate having the aromatic unit, and the trimethylolpropane; Does not contain any isocyanate polymer other than the toluene diisocyanate dimer, and does not contain any isocyanate Urethane-based hot melt adhesive.
2. The isocyanate-derived units are units derived from at least one compound selected from the group consisting of toluene diisocyanate, diphenylmethane diisocyanate, and polymeric diphenylmethane diisocyanate. The urethane-based hot melt adhesive according to claim 1.
3. the polyol-derived units are units derived from a polyester polyol comprising at least carboxylic acid-derived units and polyol-derived units; The carboxylic acid-derived unit includes the aromatic unit. The urethane-based hot melt adhesive according to claim 1 or 2.
4. The polyurethane has a crosslinked structure. The urethane-based hot melt adhesive according to any one of claims 1 to 3.
5. The catalyst accounts for 0.005% by mass or more and less than 0.08% by mass of the total amount. The urethane-based hot melt adhesive according to any one of claims 1 to 4.
6. The toluene diisocyanate dimer accounts for 1% by mass or more and 15% by mass or less of the total amount. The urethane-based hot melt adhesive according to any one of claims 1 to 5.
7. Further contains a silane coupling agent The urethane-based hot melt adhesive according to any one of claims 1 to 6.
8. The number average molecular weight of the polyurethane is in the range of 6,000 to 12,000. The urethane-based hot melt adhesive according to any one of claims 1 to 7.
Citation Information
Patent Citations
Polyisocyanate curing agent for laminating adhesive and laminating adhesive using same
JP1999080699A
Reactive hot-melt adhesive and adhesive interlining cloth using the same
JP2001026762A
Sealing tape for waterproof cloth
JP2002121514A
Adhesive for lamination and method for manufacturing laminate film
JP2003082322A
Heat-activated adhesive polyurethane powder
JP2013529238A